Pengaruh Literasi Keuangan dan Pinjaman Online Terhadap Keputusan Pengambilan Kredit Gadget Pada Erafone N More Usman Sadar Kota Gresik - Pranada, Robit; Dwi Purnomo, Arie Setyo (Management Department of Economics and Business Of Trunojoyo Madura University, 2024)
This research was motivated by the rampant use of online loan applications in purchasing gadgets at Erafone n More Usman Sadar Gresik City. The purpose of this study is to find out how financial literacy and online loans impact the decision to use electronic device credit. This study applied quantitative methods using primary and secondary data. The sample used in this study was Saturated Sampling or Census using 42 respondents. Data collection in this study used questionnaires that have been tested for validity. Multiple linear regression analysis is used to analyze the data. The T test shows that financial literacy factors affect gadget credit-making decisions, and online loans affect gadget credit-making decisions. Meanwhile, the simultaneous test (F test) shows that financial literacy factors and online loans are both very influential on gadget credit-making decisions.